Optimizing the role of pharmacists at the primary healthcare centres in Indonesia through an integrated information system - Nur Yuliasih; Yasmin Fatinah; Rizky Abdulah; Rizky Abdulah; Auliya A. Suwantika; Auliya A. Suwantika; Auliya A. Suwantika (Frontiers in Public Health)
IntroductionThe role of pharmacists at primary healthcare centers (PHCs) in Indonesia still needs long-term improvement. Enhancing interprofessional collaboration through data-driven collaboration is essential to strengthening cooperation. This study aimed to identify the need for an integrated information system to enhance the role of pharmacists at PHCs in Indonesia.MethodsA desk review was applied as the initial step to analyze the role of pharmacists at the PHCs in Indonesia. Furthermore, a qualitative study was conducted using Walt and Gilson’s health policy analysis framework. Semi-structured interviews were conducted in four sections (context, content, process, and actors) with consideration of selected key respondents. All interviews were transcribed verbatim and then analyzed using Braun and Clarke’s thematic analyses, ensuring a comprehensive understanding of the situation.ResultsWe identified two significant challenges in optimizing the use of integrated systems at the PHCs to increase the role of pharmacists. Considering context-content-process-actors, implementing integrated pharmaceutical care standards relies significantly on human resources and infrastructures. Key challenges related to human resources are a limited number of human resources, a high workload, and insufficient use of working tools. We found several challenges regarding infrastructure, such as network connectivity issues, non-integrated systems or applications, and suboptimal benefits from the current systems.ConclusionVarious systems or applications in PHC involve reporting to the Ministry of Health, but detailed integration of these systems needs to be achieved immediately. According to informants, the criteria for desired applications are crucial to optimizing the integrated system, using it, and streamlining tasks for pharmacists at PHCs. Common expectations include an integrated system for monitoring drug usage and orders. Apart from usefulness, network connectivity must be assured for accessibility by all parties.